Comparison of Three-Dimentional Scapular Position and Orientation Between Subjects with and without Shoulder Impingement - Afsoun Nodehi-Moghaddam; Esmaeil Ebrahimi; Majid Eyvazi; Mahyar Salavati (University of Social Welfare and Rehabilitation Sciences, 2006)
Objective: Epidemiologic Investigations have revealed a high prevalence (16% - 44%) of shoulder complaints consistent with "impingement" in certain occupations. Multiple theories exist in respect to the primary etiology of shoulder "impingement" such as anatomic abnormalities of the coracoacrominal arch or humeral head weakness or degeneration of the rotator cuff tendons shoulder kinematic postural abnormalities and improper scapular muscles control. comparison of kinematic parameters of shoulder complex in healthy and impingement persons. Materials & Methods: 17 patients with shoulder Impingement syndrome that were selected conveniently (age = 43.82) and 17 healthy persons that were matched with patients (age=44.5) participated in this case - control study. A three - dimentional electromechanical digitizer was used to measure scapular position and orientation. Measurments were taken while the arm placed at the side of the body and elevated 45˚, 90˚, 120˚ along with full range of motien in the scapular plane. Orientation was described by upward rotation angle, posterior tilting angle and internal rotation angle. Position was described by medio - lateral position and superio - inferior position.  Results: Comparing to non impaired subjects, those with impingement, demonstrated a significantly lower upward rotation angle (90˚ , 120˚) and posterior tilt angle of the scapla in respective scapular plane. (P<0/05) Conclusion: These results suggest that altered scapular kinematic maybe an Important aspect of the "impingement syndrome". Scapular upward Rotation and posterior tipping are important to consider in the rehabilitation of pateints with symptoms of shoulder Impingement.